PENYIMPANGAN TEORI BROWN DAN LEVINSON DALAM TINDAK TUTUR PESERTA TALK SHOW INDONESIA LAWYERS CLUB (ILC) DI TV ONE DAN RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - bukhori muslim (RETORIKA: Jurnal Ilmu Bahasa, 2017)
Abstract This research purpose to describe forms of deviation Brown and Levinson's theory of politeness in speech act participant Indonesia Lawyers Club on TV One and its relevance to the Indonesian language learning in high school. The theory is used to solve the problem in this research is the pragmatic theory. While the approach used is descriptive qualitative approach with data collection technique is a technique of documentation and observation. The results showed that the forms of deviations Brown and Levinson's theory of politeness that occur in the speech act participant Indonesia Lawyers Club edition of May 27, 2014 and 7 April 2015 consisted of threatening the positive face and negative face threats. Participants utterances that threaten positive face expression covers complaints, charges, disapproval, criticism, expressions that do not koopratif, embarrass opponents said, and words taboo. While the band is used in the expression of negative advance threatening the expression of rejection, suggestions, advice, requests, prohibitions, promises and praise. Types of speech acts band is used that speech acts directive, declarative, expressive, and refresentatif. Meanwhile, the offense Brown and Levinson’s theory in speech acts ILC participants more based on an awareness for justice, self-defense, solidarity groups, power, recognition of self and groups, law enforcement, the fight against corruption and advocacy on behalf of the people. Relevance of the research results can be applied in learning Indonesian in class XI SMA second half, KD 9. 2 with the subject matter by providing comments on the discussion.